A Review of Creatine Supplementation: Side Effects and Improvements in Athletic Performance - Andres, L. P. A.; Sacheck, J. M.; Tapia, S. (Nutrition and Clinical Care, 1999)
Creatine is a popular ergogenic aid that is sold as a nutrition supplement. Research has shown that creatine supplementation may improve performance during intermittent bouts of high-intensity exercise, while there do not appear to be any benefits during endurance-type athletic events. Information on the risks associated with this product is scarce. Although there are anecdotal reports of gastrointestinal distress associated with creatine supplementation, there have been no peer-reviewed studies of high-dose creatine supplementation lasting longer than ten weeks in healthy subjects. However, it is recommended that children, adolescents, pregnant women, and people with diabetes or renal disease avoid creatine supplementation due to its unknown effects on these special populations. This review includes a description of the metabolic role of creatine and the effects of supplemental doses on skeletal muscle, as well as an examination of the potential physiological mechanisms, effectiveness, and side effects of creatine supplementation.